Synthesis of Carbon Quantum Dots and Their Optical Properties Under Various Conditions - Dhobi, Saddam; Hangsarumba, Surendra; Kamat, Raman Kumar; Yadava, Kishori; Gupta, Suresh Prasad (Jurnal Fisika, 2025)
Carbon quantum dots (CQDs) are nanomaterials that possess great optical properties, and they hold potential for being used in biosensing, imaging, and optoelectronics. The aim of this work is to synthesis, characterization and study the optical properties of CQDs under various condition. In the present work, CQDs have been prepared by mixing equal amount (citric acid and urea) and heating in microwave at 165 °C-180 oC for 2 min to obtained dark brown color. The dark brown power was characterizations using FTIR to confirmed the different functional groups such as –P–O, –S–O, – O–C, C=C C=N and CH2/CH3 (oxygenated-, nitrogenated- and aromatic-types), while XRD analysis indicated the valuable crystalline organic phases with heterogeneous functionality features. The optical properties were carried out in water and sugar solutions (100–155mg/dl) as function of CQDs concentration, temperature, frequency and UV activation times using a Theremino spectrometer. The fluorescence intensity was enhanced with the increase of citric acid and was quenched by urea. In sugar at higher CQD concentrations, intensity was decreased from molecular trapping and light scattering. The fluorescence intensity exhibited fluctuations in water during 60s with red and blue-shifts, and the maximum peak was at 545 nm. The intensity increased with decreasing CQD: water ratio and decreased at higher concentrations, because of absorption and scattering. The temperature and frequency have strong effects on the optical responses; the higher temperatures (58 °C) promote dispersed aggregates in finer particles which leads to more light transmission in addition to larger absorption values at higher frequencies. This demonstrated the tunable features of CQDs optical properties and might give suggestions for subsequent optimization for their applications in biosensing, imaging, and optoelectronics.